Successful liver transplantation from a donor with occlusive portal vein thrombosis - M. S. Novruzbekov; O. D. Olisov; V. A. Gulyaev; K. N. Lutsyk; B. I. Yaremin; B. I. Kazymov; K. M. Magomedov; A. R. Akhmedov; K. F. Alekberov (Трансплантология (Москва), 2023)
Introduction. The shortage of donor organs has been and remains the basic problem of clinical transplantation and the expansion of the organ pool by using marginal donor organs has become one of its solutions. In this regard, every decision to use a "non-standard" or "non ideal" organ for transplantation should be made carefully.Aim. Demonstration of successful liver transplantation from a donor with brain death and occlusive thrombosis of the splanchnic venous system.Description. A 34-year-old donor without serious concomitant pathology was diagnosed with total portal thrombosis during liver procurement. After cold aortic perfusion, a thrombectomy from the portal vein was performed. At the “backtable” stage, an additional perfusion was made through the portal vein, the results of which confirmed the patency of the portal system. The liver graft was transplanted to a 33-year-old recipient; the postoperative period was uneventful, the patient was discharged on the 17-th postoperative day.Conclusions. Portal vein thrombosis in a donor liver is rare. A positive decision on liver transplantation from a donor with portal vein thrombosis should be based on the confirmed patency of the portal system. It is desirable that these data be supplemented by a histological examination of the donor liver. The donor organs shortage needs to expand the criteria for post-mortem organ donation. However, every decision should be made in the light of individual characteristics of the donor-recipient pair.